A Study on the High Load Operation of a Natural Gas-Diesel Dual-Fuel Engine - Dev, Shouvik; Guo, Hongsheng; Liko, Brian (Frontiers in Mechanical Engineering, 2020)
Diesel fueled compression ignition (CI) engines are widely used in power generation and freight transport owing to their high fuel conversion efficiency and ability to operate reliably for long periods of time at high loads. However, such engines generate significant amounts of carbon dioxide (CO2), nitrogen oxides (NOx), and particulate matter (PM) emissions. One solution to reduce the CO2 and PM emissions of diesel engines while maintaining their efficiency and reliability is natural gas (NG)-diesel dual-fuel combustion. In addition to methane emissions, the temperatures of the diesel injector tip and exhaust gas can also be concerns for dual-fuel engines at medium and high load operating conditions. In this study, a single cylinder NG-diesel dual-fuel research engine is operated at two high load conditions (75% and 100% load). NG fraction and diesel direct injection (DI) timing are two of the simplest control parameters for optimization of diesel engines converted to dual-fuel engines. In addition to studying the combined impact of these parameters on combustion and emissions performance, another unique aspect of this research is the measurement of the diesel injector tip temperature which can predict potential coking issues in dual-fuel engines. Results show that increasing NG fraction and advancing diesel DI timing can increase the injector tip temperature. With increasing NG fraction, while the methane emissions increase, the equivalent CO2 emissions (cumulative greenhouse gas effect of CO2 and CH4) of the engine decrease. Increasing NG fraction also improves the brake thermal efficiency of the engine though NOx emissions increase. By optimizing the combustion phasing through control of the DI timing, brake thermal efficiencies (BTEs) of the order of ~42% can be achieved. At high loads, advanced diesel DI timings typically correspond to the higher maximum cylinder pressure, maximum pressure rise rate, BTE and NOx emissions, and lower soot, CO, and CO2-equivalent emissions.